Secondary traumatic stress in emergency department nurses: A multi-methods study protocol - Mahdieh Motie; Masoud Fallahi-khoshknab; Farahnaz Mohammadi Shahbolaghi; Mohammad Saeed Khanjani; Marcus Stueck; Hamidreza Khankeh (Journal of Research Development in Nursing and Midwifery, 2025)
Background: Secondary traumatic stress (STS) is a psychological phenomenon that refers to the negative and traumatic emotional experiences that individuals endure as a result of exposure to the pain and suffering of others, particularly in caring professions such as emergency nursing. STS not only affects the mental health of nurses but can also have a significant impact on the healthcare system. We will conduct this study to explore the phenomenon of STS in depth and compile a policy brief. Methods: This study employs a multi-methods approach, integrating a grounded theory study, a systematic scoping review, and the Delphi method, culminating in the development of a policy brief. Grounded theory, recommended by Corbin and Strauss (2014), will be used to explore the process of STS among emergency nurses through individual interviews and observations. Participants will be selected using purposive and theoretical sampling until data saturation is achieved. Data collection will focus on emergency nurses' experiences and emotional responses, with analysis proceeding through five stages: open coding, concept development, contextual analysis, process analysis, and category integration. The second phase is a systematic scoping review exploring challenges in managing STS among emergency nurses. This review will synthesize national and international experiences, based on Arksey and O’Malley’s five-step framework and the PRISMA model to systematically collect and integrate findings. The results from the grounded theory, including identified concepts, facilitators, and barriers, will be integrated with the scoping review findings using the classical Delphi method. A panel of expert nurses and scholars will engage in iterative Delphi sessions to refine perspectives on STS in emergency nursing. Finally, a policy brief will be developed, synthesizing key findings and providing evidence-based recommendations for policymakers. Conclusion: This study protocol offers a comprehensive guide for conducting a multi-methods study, outlining the research process step-by-step to aid researchers using similar methodologies. It addresses common language-related challenges, suggests solutions, and helps deeply explore the phenomenon of STS and compile a policy brief. The protocol emphasizes maintaining high research integrity through specific criteria and provides a detailed discussion of ethical considerations and research methodology. The authors advocate for publishing multi-methods protocols before implementation to improve research integrity, foster ethical and integrated practices, and support novice researchers.